The Ultimate Ratio

Calculus Level 5

0 , 0 , 1 , 1 , 2 , 4 , 7 , 13 , 24 , 44 , 81 , \large 0, 0, 1, 1, 2, 4, 7, 13, 24, 44, 81,\cdots

Let T n T_n be the n n th term of the given sequence and L = lim n T n + 1 T n \displaystyle L=\lim_{n\to\infty}\dfrac{T_{n+1}}{T_n} .

Find 8 cos ( 3 cos 1 3 L 1 4 ) 8\cos\left(3\cos^{-1}\dfrac{3L-1}{4}\right) .


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Joseph Newton
Apr 16, 2018

The sequence is called the ' Tribonacci numbers ', and each term is equal to the sum of the previous 3 terms (i.e. T n = T n 1 + T n 2 + T n 3 T_n=T_{n-1}+T_{n-2}+T_{n-3} ).

(Note: the Brilliant wiki and the Wolfram Mathworld page for the Tribonacci numbers have the sequence starting with 1 zero while the Online Encyclopedia of Integer Sequences and Wikipedia have the sequence starting with 2 zeros. This does not affect the solution to this question.)

Assuming that the series approaches a common ratio L = lim n T n + 1 T n \displaystyle L=\lim_{n\to\infty}\dfrac{T_{n+1}}{T_n} , we can consider 4 very large consecutive terms in the series, a , b , c a,b,c and d d , so that: a + b + c = d and b a = c b = d c = L a+b+c=d\qquad\text{and}\qquad\frac{b}{a}=\frac{c}{b}=\frac{d}{c}=L Solving these equations, we can get a cubic equation for L: c b = b a d c = b a c = b 2 a d = b c a d = b 3 a 2 a + b + c = d a + b + b 2 a = b 3 a 2 b 3 a 3 b 2 a 2 b a 1 = 0 L 3 L 2 L 1 = 0 \begin{aligned}\frac{c}{b}&=\frac{b}{a}&\frac{d}{c}&=\frac{b}{a}\\ c&=\frac{b^2}{a}&d&=\frac{bc}{a}\\ &&d&=\frac{b^3}{a^2}\\ a+b+c&=d\\ a+b+\frac{b^2}{a}&=\frac{b^3}{a^2}\\ \frac{b^3}{a^3}-\frac{b^2}{a^2}-\frac{b}{a}-1&=0\\ L^3-L^2-L-1&=0\end{aligned} To solve this, we will first remove the squared term by letting L = y + 1 3 L=y+\frac{1}{3} : ( y + 1 3 ) 3 ( y + 1 3 ) 2 ( y + 1 3 ) 1 = 0 ( y 3 + y 2 + 1 3 y + 1 27 ) ( y 2 + 2 3 y + 1 9 ) ( y + 1 3 ) 1 = 0 3 y 3 4 y 38 9 = 0 \left(y+\frac{1}{3}\right)^3-\left(y+\frac{1}{3}\right)^2-\left(y+\frac{1}{3}\right)-1=0\\ \left(y^3+y^2+\frac{1}{3}y+\frac{1}{27}\right)-\left(y^2+\frac{2}{3}y+\frac{1}{9}\right)-\left(y+\frac{1}{3}\right)-1=0\\ 3y^3-4y-\frac{38}{9}=0 Now, instead of continuing with Cardano's method, we will let y = 4 3 cos θ y=\frac{4}{3}\cos\theta : 3 ( 4 3 cos θ ) 3 4 ( 4 3 cos θ ) 38 9 = 0 64 9 cos 3 θ 16 3 cos θ 38 9 = 0 4 cos 3 θ 3 cos θ 19 8 = 0 3\left(\frac{4}{3}\cos\theta\right)^3-4\left(\frac{4}{3}\cos\theta\right)-\frac{38}{9}=0\\ \frac{64}{9}\cos^3\theta-\frac{16}{3}\cos\theta-\frac{38}{9}=0\\ 4\cos^3\theta-3\cos\theta-\frac{19}{8}=0 Using the trigonometric identity cos 3 θ = 4 cos 3 θ 3 cos θ \cos3\theta=4\cos^3\theta-3\cos\theta :* cos 3 θ 19 8 = 0 cos 3 θ = 19 8 \cos3\theta-\frac{19}{8}=0\\ \cos3\theta=\frac{19}{8} This has no real solutions, but there are complex ones, so we can still find the answer to the question with some rearranging: L = y + 1 3 L 1 3 = 4 3 cos θ 3 L 1 4 = cos θ cos 1 3 L 1 4 = θ 3 cos 1 3 L 1 4 = 3 θ cos ( 3 cos 1 3 L 1 4 ) = cos 3 θ = 19 8 8 cos ( 3 cos 1 3 L 1 4 ) = 19 \begin{aligned}L&=y+\frac{1}{3}\\ L-\frac{1}{3}&=\frac{4}{3}\cos\theta\\ \frac{3L-1}{4}&=\cos\theta\\ \cos^{-1}\frac{3L-1}{4}&=\theta\\ 3\cos^{-1}\frac{3L-1}{4}&=3\theta\\ \cos\left(3\cos^{-1}\frac{3L-1}{4}\right)&=\cos3\theta\\ &=\frac{19}{8}\\ 8\cos\left(3\cos^{-1}\frac{3L-1}{4}\right)&=\boxed{19}\end{aligned}


*Concerning the trigonometric substitution

This is how one would determine what to let y equal for this trigonometric substitution to work:

We are going to let y = k cos θ y=k\cos\theta . The cubic expression equals zero, so we can multiply it by whatever we want, so it's simply a matter of finding a value of k such that the ratio between the coefficient of y 3 y^3 and the coefficient of y y is 4:3.

When we substitute in, the 3 y 3 3y^3 will become 3 k 3 cos 3 θ 3k^3\cos^3\theta and the 4 y 4y will become 4 k cos 3 θ 4k\cos^3\theta , so to make the ratio work: 3 k 3 4 k = 4 3 k 2 = 16 9 k = 4 3 \frac{3k^3}{4k}=\frac{4}{3}\\ k^2=\frac{16}{9}\\ k=\frac{4}{3} Now when we do the substitution we will be able to use the formula cos 3 θ = 4 cos 3 θ 3 cos θ \cos3\theta=4\cos^3\theta-3\cos\theta and solve the equation.

Great solution

Anand Badgujar - 3 years, 1 month ago

Excellent solution!!!

Rahul Singh - 3 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...